The effects of using language games in teaching grammar among lower secondary school students of different gender / Ruzilah Md Sharif - Md Sharif, Ruzilah (2012)
Using language games in ESL classroom may be one of the alternatives to encourage students to engage in class activity and at the same time to improve their proficiency levels. This study was conducted to examine the effects of using language games in teaching grammar and also to find out the students' performance in pre-test and post test of the experimental and control groups. For this purpose, a total of 56 Form Two students studying at Sekolah Menengah Kebangsaan Seksyen 16, Shah Alam Selangor were chosen as samples. The samples were assigned to either experimental or control groups in which the experimental group used language games in learning grammar, while the control group learning grammar in a traditional way. Data gathered from the pre -test and post-test were analysed descriptively. In addition, two set s of questionnaire were given to the experimental group to see their attitudes and motivation towards language games and games used in learning grammar. The findings show that there is significant difference in the scores between students taught using language games and students taught using traditional method, F (1,54) = 62.930, P < .05. However, the findings show that there is no significant difference between male and female students in the scores of the experimental group, F (1,26) = .376, p > .05. The findings also show that there is a correlation between students' scores and their level of motivation towards the games used in learning grammar (u = .037). Finally, the findings show that language games bring positive impact towards students' attitudes and motivation towards learning grammar. The study suggests that while students accept the effectiveness of using language games in learning the simple present tense and the simple past tense; there were some other aspects of grammar to be put into consideration in mastering English language. Recommendations for future studies and solutions were discussed. Hopefully, this study would be able to provide some useful insights for effective implementation of language games in ESL classroom.